PENGARUH PRICE EARNING RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA INDUSTRI TELEKOMUNIKASI DI BURSA EFEK INDONESIA PERIODE 2011-2014 - M Zahari; Ubaidillah Ubaidillah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
This study aimed to test to influence Price Earning Ratio (PER) and Earning Per Share (EPS) on stock price at industry telecommunication in indonesia stock exchange during the periode 2011-2014. The independent variabel studied were Price Earning Ratio (PER) and Earning Per Share (EPS) on stock price at industry telecommunication in indonesia stock exchange. The analytical method used is multiple linear regression analysis, the classical assumption (normality, multicollininearity , autocorrelation and heteroskedasitas), hypothesis testing (F test and t test), and the coefficient of determination. Based on the result of multiple regression analysis showed that the PER and EPS simultaneosly significant effect on stock price, amounting to 64,8% and the reamining 35,2% influenced by other factors beyond the research the Adjust R Square value of 0,648. In partial, PER does not effect the stock price while the variabel EPS partially significant effect on stock prices. Conclusion this study shows that regression model is formed by the independent variabel consisting of PER and EPS can be used to predict the stock price on the industry Telecommunication in indonesia Stock Exchange.Keyword: price earning ratio, earning per share